Predictive value of electrocardiographic markers in children with dilated cardiomyopathy - Wang, Miao; Xu, Yi; Wang, Shuo; Zhao, Ting; Cai, Hong; Wang, Yuwen; Zou, Runmei; Wang, Cheng (Frontiers in Pediatrics, 2022)
Dilated cardiomyopathy (DCM) refers to a heterogeneous group of cardiomyopathies characterized by ventricular dilatation and myocardial systolic dysfunction, which can lead to serious consequences such as malign arrhythmia, sudden death, heart failure, and thromboembolism. With its economical, non-invasive, simple and reproducible advantages, electrocardiogram (ECG) has become an important indicator for assessing the prognosis of cardiovascular diseases. In recent years, more and more studies of electrocardiography on DCM have been carried out, but there is still a lack of a comprehensive summary of its prognostic value. This article reviews the prognostic value of electrocardiographic markers in children with DCM.